學生選擇多元入學管道因素之探討：以四技為例 Factors Influencing Students' Choices in the Multiple College Entrance Program: The Case of Four-Year Institutes of Technology - 林大森 Da-Sen Lin (National Taiwan Normal University, 2010)
關於「大學多元入學方案」的相關討論，為近年來相當重要的研究議題。雖然累積了很多成果，但關注於技職體系的學術研究則相當罕見。本文以高等技職教育體系（四技）為研究對象，採用「臺灣高等教育資料庫」九十四學年度四技新生資料，分析家庭背景、高中職經歷如何影響個人選擇推薦甄選、登記分發、申請入學三大入學管道。研究發現：一、父母教育程度較高者，經由申請入學機會較大；二、相較於登記分發，推薦甄選以及申請入學者，較重視師長與親友之建議；三、人文學門中，推薦甄選途徑者較大機會錄取公立技職院校，而申請入學者則是在自然學門較容易考上公立技職院校。 One of the most widely investigated research topics in recent years concerns student participation in the Multiple College Entrance Program. Although many researchers have examined this topic, few studies have examined how this issue relates to students studying in the technological and vocational education system. The present study examined students studying in four-year institutes of technology. Utilizing a survey of freshmen conducted in 2005 as part of the Taiwan Higher Education Database, the present study analyzed how family background and high school experiences affected students' choices for the three major channels of admission: recommendation and screening, registration and placement, and application. The main findings were: (1) Students whose parents have a higher than average level of education have more opportunities to apply for university by application. (2) Students who take advantage of the recommendation and screening or application admission channels are likely to rely on teachers' and friends' suggestions or opinions. (3) For departments in the fields of arts and humanities at public institutes of technology, more students entered via the recommendation and screening channel. At the same time, applicants are easily allowed for applications to public Institute of Technology in departments of Sciences.